Heuristic Scheduling in a Woolen Mill - Hurst, E. Gerald; McNamara, Aidan B. (Management Science, 1967)
The scheduling procedure of a particular production planner in a woolen mill is investigated. A model is developed which attempts to describe the planner's average behavior. Schedules are generated by this model and are compared with the corresponding schedules of the planner. Discrepancies between the planner's and the model's schedules are interpreted with respect to both the adequacy of the model and the consistency of the planner. Suggestions are made for application of the technique to real-time scheduling.